Analysis Of Narcotics Crime Group I Is Not A Plant In Decision No. 252/PID.SUS / 2025 / PN TBT - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2026)
The abuse of class I non-crop narcotics in Indonesia has reached alarming levels and requires comprehensive legal treatment. This study analyzed the Tebingtinggi District Court decision number 252 / Pid.Sus/2025/PN Tbt to understand the application of criminal law in the case of possession of methamphetamine weighing 1.18 grams. Normative juridical research methods are used by examining positive legal norms and their application through literature studies of primary, secondary, and tertiary legal materials. The results showed that the panel of judges managed to prove the elements of Article 112 paragraph (1) of Law No. 35 of 2009 systematically, where the defendant was proven to possess narcotics without legitimate rights. Juridical considerations reflect the application of the principle of legality by distinguishing acts of circulation and ownership, so that subsidiary charges are more appropriately applied. The verdict of five years imprisonment and a fine of one hundred million rupiah shows the proportionality between the weight of the act and the sanctions imposed. The study concluded that the verdict has met the principles of legal certainty and substantive justice, but the rehabilitative approach needs to be optimized to distinguish traffickers and users in order to realize a justice system that is not only repressive but also restorative.